2010
DOI: 10.1016/j.cplett.2010.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface coating on the toxicity of silver nanomaterials on human skin keratinocytes

Abstract: As nanotechnology field continues to develop, assessing nanoparticle toxicity is very important for advancing nanoparticles for daily life application. In this Letter, we report the effect of surface coating on cyto, geno and photo-toxicity of silver nanomaterials of different shapes on human skin HaCaT keratinocytes. We found that the citrate coated colloidal silver nanoparticles at 100 µg/mL level are not geno-, cyto- and phtotoxic. On the other hand, citrate coated powder form of the silver nanoparticles ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
150
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(163 citation statements)
references
References 25 publications
5
150
1
7
Order By: Relevance
“…MHA@AgNPs, indicating the surface coating could obviously mediate the antibacterial activities of AgNPs. The surface coating effect that was previously reported indicated that citrate-coated AgNPs exerted higher toxicities when compared to those coated with biodegradable polymer, 29 although no differences were observed between AgNPs with polyvinylpyrrolidone or oleic acid coatings in an earthworm study. 30 The antibacterial order observed was exactly consistent with the trend of silver ion release from these AgNPs (Figure 2).…”
mentioning
confidence: 64%
“…MHA@AgNPs, indicating the surface coating could obviously mediate the antibacterial activities of AgNPs. The surface coating effect that was previously reported indicated that citrate-coated AgNPs exerted higher toxicities when compared to those coated with biodegradable polymer, 29 although no differences were observed between AgNPs with polyvinylpyrrolidone or oleic acid coatings in an earthworm study. 30 The antibacterial order observed was exactly consistent with the trend of silver ion release from these AgNPs (Figure 2).…”
mentioning
confidence: 64%
“…These results suggested reversible toxicity of Ag NPs and a transient discoloration of exposed skin. Lu et al [38] reported the effect of surface coating on cyto, geno and photo-toxicity of silver nanomaterials of different shapes on human skin HaCaT keratinocytes. They demonstrated that coating of silver NPs with a biodegradable polymer prevents the toxicity of the power.…”
Section: Penetration Of Metal Npsmentioning
confidence: 99%
“…Various applications of silver nanoparticles to vegetables (An, Zhang, Wang, & Tang, 2008;Costa, Conte, Buonocore, & Del Nobile, 2011;Fayaz, Balaji, Girilal, Kalaichelvan, & Tvenkatesan, 2009;Hu, Fanga, Yang, Ma, & Zhao, 2011;Zhang, Duan, & Shan, 2005) and dairy products (Incoronato, Conte, Buonocore, & Del Nobile, 2011) are reported in the literature. As toxicological features of silver nanoparticles are well known (Kiruba, S.C.G., Tharmaraj, Sironmanic, & Pitchumani, 2010;Lu et al, 2010), EU safety regulation limits silver amount to 0.05 mg Ag/kg of food (Fernandez et al, 2009). Thus, due to the safety concern, the use of food coatings as carriers of silver represents a viable approach to avoid the direct contact of nanoparticles with food (Gammariello, Conte, Buonocore, & Del Nobile, 2011;Incoronato et al, 2011).…”
Section: Introductionmentioning
confidence: 99%